2014
DOI: 10.1074/jbc.m114.593897
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Rearrangements in the Pro-apoptotic Protein, Bax, as It Inserts into Mitochondria

Abstract: Background:The translocation of pro-apoptotic protein Bax from the cytosol to the mitochondria signals the commitment to cell death. Results: Distances between locations in Bax were measured during translocation in live cells. Conclusion:The conformational changes that coincide with the commitment to apoptosis were identified. Significance: This information is crucial for the development of more effective therapeutics that target apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
91
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 36 publications
(47 reference statements)
14
91
2
Order By: Relevance
“…An α9:α9 interface in Bak (and Bax) oligomers was demonstrated by linkage of the α9 helices after pore formation, consistent with very recent evidence of an α9:α9 interface in Bax oligomers, Figure 3a, or for cytochrome c release based on Förster resonance energy transfer (FRET) 29 and crosslinking. 67 A distinct cysteine linkage pattern along α9 was not due to a dimerization domain, but may be caused by a preferred packing surface between the helices and/or by limited rotation of α9 within oligomers.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…An α9:α9 interface in Bak (and Bax) oligomers was demonstrated by linkage of the α9 helices after pore formation, consistent with very recent evidence of an α9:α9 interface in Bax oligomers, Figure 3a, or for cytochrome c release based on Förster resonance energy transfer (FRET) 29 and crosslinking. 67 A distinct cysteine linkage pattern along α9 was not due to a dimerization domain, but may be caused by a preferred packing surface between the helices and/or by limited rotation of α9 within oligomers.…”
Section: Discussionsupporting
confidence: 87%
“…67 Notably, Bleicken et al 67 suggested the α9:α9 interaction 'within' dimers may be anti-parallel based on a model in which the α2-α5 core dimers position on the rim of the pore rather than facing the cytosol. Although our linkage studies and the FRET studies of Gahl et al 29 show parallel interaction of the α9 helices, we may be detecting interactions 'between' dimers (as depicted in Figure 7d) and not the interactions that might occur 'within' dimers.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Analysis of the active Bax membrane topology suggests that the TMD could play a central role in Bax oligomerization (26). Förster resonance energy transfer studies have shown that Bax forms homooligomers in the mitochondria through TMD interactions (27). Bcl-x L -mediated Bax retrotranslocation into the cytosol depends on the Bcl-x L TMD, suggesting the involvement of TMD interactions in Bax inhibition (13).…”
mentioning
confidence: 99%